Secure Pesticide Storage: Security Against Terrorist Threats - Frederick M. Fishel (EDIS)
Many farmers and managers of pesticide storage facilities had concerns about biosecurity and agroterrorism even before the Oklahoma City bombing and the September 11, 2001 terrorist attacks on our nation. Businesses that manufacture, reformulate, sell, distribute, transport, store, or apply pesticides have long known the mitigation steps for safety of their workers, customers and communities. In todays age, these efforts may not necessarily be enough. This document is PI-42, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 2005.